CARACTERIZACIÓN DE NEUMONÍA POR STAPHYLOCOCCUS AUREUS METICILINO RESISTENTE EN HOSPITAL MILITAR DE ALTA COMPLEJIDAD - Ramon Medina-Mur (Asociación Colombiana de Infectología, 2018)
Introduction: Strains methicillin-resistant Staphylococcus aureus (MRSA), to be resistant to most beta-lactam available and different families of antibiotics, represent a major challenge in therapeutics; for this reason, it is necessary to conduct studies to characterize better patients with MRSA infection. Methods: A descriptive study of cross section of patients diagnosed with bacterial pneumonia with positive microbiological isolation for MRSA was conducted by reviewing medical records and susceptibility testing relevant demographic and clinical data were extracted. The data analysis was conducted through measures of central tendency and dispersion. Results: During the period of 4 years of study; there were 211 isolates corresponding to S. aureus; of which 22 were for MRSA bacterial pneumonia. Nosocomial pneumonia was the most common presentation (54,5%); followed by community-acquired pneumonia (36,3%). 36,3% of patients were military personnel, 31,8% retired military or civilians. The frequency of comorbidities was 92,3% being chronic kidney disease and the most common malignancy. Conclusion: From the clinical point of view MRSA pneumonia it was characterized by a greater number of young patients without comorbidities; which contrasted with nosocomial pneumonia was characterized by an aging population and higher prevalence of comorbidities.